Photoluminescence studies of cubic GaN epilayers. Issue 8 (21st February 2017) - Church, S. A.; Hammersley, S.; Mitchell, P. W.; Kappers, M. J.; Sahonta, S. L.; Frentrup, M.; Nilsson, D.; Ward, P. J.; Shaw, L. J.; Wallis, D. J.; Humphreys, C. J.; Oliver, R. A.; et al.
Abstract: The luminescence properties of cubic GaN films grown upon 3C‐SiC/Si (001) substrates by MOCVD were investigated. The spectra show luminescence peaks which are associated with donor bound exciton recombination and donor acceptor pair recombination. A reduced peak energy for the D 0 X emission compared with values reported in the literature suggests a tensile‐strain‐reduced bandgap of approximately 3.27 eV, which is consistent with the absorption edge in photoluminescence‐excitation spectroscopy. The presence of hexagonal material introduces a broad emission band at 3.40 eV with a FWHM of 190 meV, extending to energies up to 3.60 eV. The intensity of this emission scales linearly with excitation power, its peak energy and width remaining unchanged. This band is associated with an absorption edge below 3.70 eV and therefore is not caused by absorption into phase‐pure cubic or hexagonal GaN. The photoluminescence lifetimes measured across this band reduce from 0.40 to 0.20 ns with increasing emission energy. All these observations can be explained by considering a type‐II‐band alignment adjacent to stacking faults within the cubic GaN.